Development, validation, and application of an UPLC-MS/MS method for vancomycin, norvancomycin, methotrexate, paclitaxel, and imatinib analysis in human plasma. (July 2022) - Chen, Xinran; Du, Liying; Liu, Mingfeng
Background: Vancomycin, norvancomycin, methotrexate, paclitaxel, and imatinib are five commonly used drugs which are all recommended to therapeutic drug monitoring in clinical settings. However, the blood concentration monitoring of these drugs and the interpretations of the test results are limited to some extent due to the differences of testing instruments and testing methods. Methods: We established an ultra-performance liquid chromatography with tandem mass spectrometry (UPLC-MS/MS) method for simultaneous quantification of vancomycin, norvancomycin, methotrexate, paclitaxel, and imatinib in human plasma. The method was validated according to the guideline for bioanalytical method validation and applied in clinical therapy. Results: The calibration ranges of vancomycin, norvancomycin, methotrexate, paclitaxel, and imatinib were 0.5–100 μg/mL, 0.5–100 μg/mL, 5–1000 ng/mL, 10–2000 ng/mL, and 5–500 ng/mL, respectively. Inaccuracy and imprecision of every drug were less than 15%. The internal standard normalized recovery rates of vancomycin and norvancomycin were about 45%, while which of methotrexate, paclitaxel, and imatinib were almost 100%. No obvious carryover effect was observed. Samples were stable for at least 24 h in the automatic sampler, 72 h at 4°C, and 1 week in −80°C. There were no differences of concentrations between plasma and serum for the five drugs. Moreover, there were positive correlations between methotrexate and vancomycin concentrations and creatinine, as well as positive correlation between imatinib concentration and age of the patient. Conclusions: The UPLC-MS/MS method was competent for the simultaneous monitoring of vancomycin, norvancomycin, methotrexate, paclitaxel, and imatinib because of its short analysis time, high specificity, and accuracy.